Enhancing indoor air quality resilience in social housing: Investigating temperature and humidity effects on HCHO emissions in Dubai - Jung, Chuloh; El Samanoudy, Gamal; Abdelaziz Mahmoud, Naglaa Sami (Frontiers in Built Environment, 2025)
Indoor air quality (IAQ) is a critical determinant of public health, particularly in rapidly urbanizing regions where residents spend most of their time indoors. Formaldehyde (HCHO), a pollutant released from building materials and furnishings, has been linked to respiratory problems and sick building syndrome, making its control essential for sustainable housing. This study investigates the relationships between HCHO emissions and temperature and humidity in newly constructed residential houses in Dubai, utilizing single-point measurements in 50 houses and continuous monitoring in three representative houses. A distinctive feature of this research is the integration of large-scale cross-sectional data with continuous temporal monitoring, applied in the context of Dubai’s housing, to capture both spatial and temporal dynamics of emissions under actual residential climate control practices. In contrast to controlled laboratory simulations, the study evaluates emissions under artificially and autonomously regulated indoor climates. Results show that in artificially controlled environments (temperatures maintained below 25 °C), HCHO emissions correlate weakly with temperature but strongly with relative humidity, with concentrations increasing when RH falls below approximately 40%. Conversely, in autonomously controlled environments (temperatures above 25 °C), temperature becomes the dominant factor, with emissions increasing as the temperature rises. This dual dependency underscores the need for adaptive IAQ strategies tailored to both seasonal conditions and household management practices. By integrating temporal and spatial data, the study highlights the role of housing characteristics and management history in shaping emission behavior and outlines applicable, low-energy strategies to support resilient IAQ management frameworks aligned with sustainability goals for social housing in the Arabian Gulf.